PEMANFAATAN KULIT DAGING BUAH KOPIFERMENTASI (DENGAN MIKROORGANISME LOKAL) DALAM PAKAN TERHADAP KONDISI DAN PERKIRAAN BOBOT KERBAU MURRAH JANTAN (Bubalus bubalis) - ENOS SEMBIRING (Universitas Sumatera Utara, 2013)
ABSTRACT Fermented pod coffee with local microorganisms can increasing the protein of feed on the implications of improved feed quality. This study aimed to determine the effects of fermented pod coffee with local microorganisms in feed to condition and estimate weight of murrah buffalo bulls (Bubalus bubalis). The research was conducted at the Balai Pembibitan Ternak Unggul Babi dan Kerbau in Silangit village, Siborong-borong Subdistrict at North Tapanuli District, North Sumatra Province on April-September 2012. This research used Latin square design (RBSL) were consist of 4 treatments. The treatments were P0 (20% unfermented pod coffee), P1 (10% fermented pod coffee), P2 (20% fermented pod coffee) and P3 (30% fermented pod coffee).The results showed that the usage of various level fermented pod coffee with local microorganisms gived significantly different effect (P <0.05) on feed intake, body condition based on bony ribs and hip bones. Chest circumference and body length were significantly (P <0.01) to the weight estimate of Murrah buffaloes. It can be concluded that fermented pod coffee can be used as feed of Murrah buffalo. Keywords : fermented pod coffee, local microorganisms, body condition, Weights estimated, Murrah buffalo